Antitrust immunity for airline alliances - Volodymyr Bilotkach; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The market developments in international air transportation have led to the dominance of three global airline alliances - Star, SkyTeam and oneworld. At the same time, members of these alliances receive increasingly more freedom in coordinating various aspects of joint operations, including scheduling and pricing decisions, as well as the right to form revenue-sharing joint ventures in international markets. Although the significant consumer benefits generated by airline cooperation are undisputed, the recent developments raise antitrust concerns. Against this background, the paper compares the key competitive effects of airline alliances and antitrust immunity with the economic lines of reasoning in recent policy actions to develop recommendations for a full-fledged assessment of antitrust immunity for airline alliances.
Keywords: L41; L93; K21; 330; Luftverkehrsgesellschaft; Strategische Allianz; Wettbewerbsbeschränkung; Konzentrationspolitik; Welt